Monetary-Fiscal Policy and Economic Growth - Smith, Warren L. (Quarterly Journal of Economics, 1957)
Introduction, 36 — I. Growth requirements, 36. — II. Growth tendencies, 39. — III. Relation between growth requirements and growth tendencies, 45. — IV. Monetary-fiscal policy and the growth rate, 47. — V. Some further complications and qualifications, 51. — VI. Concluding comments, 55.